Surface Acoustic Wave Sensor for Selective Multi-Parameter Measurements in Cardiac Magnetic Field Detection - Hongbo Zhao; Chunxiao Jiao; Qi Wang; Chao Gao; Jing Sun (Applied Sciences)
Measuring parameters like heart temperature, heart rate, and cardiac magnetic field aids in analyzing cardiac health and disease. A multi-parameter sensor tailored to the heart can significantly enhance convenience in medical diagnosis and treatment. This work introduces a multi-parameter sensor based on Surface Acoustic Wave Sensors (SAWSs) and magnetostrictive materials, designed to selectively measure various cardiac parameters. SAWSs are characterized by their compact dimensions, which facilitate integration into various medical devices. The wireless and passive characteristics of the sensors enable flexibility in the detection process. This sensor can detect various common physical quantities like weak magnetic fields by the control variable method, ensuring a high degree of accuracy. The working mode of SAWSs is investigated in this study, and the relationship curve concerning various influencing factors is established.